2022
DOI: 10.1080/21655979.2021.1996747
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory network controls microbial biofilm development, with Candida albicans as a representative: from adhesion to dispersal

Abstract: Microorganisms mainly exist in the form of biofilm in nature. Biofilm can contaminate food and drinking water system, as well as cause chronic wound infections, thereby posing a potential threat to public health safety. In the last two decades, researchers have made efforts to investigate the genetic contributors control different stages of biofilm development (adherence, initiation, maturation, and dispersal). As an opportunistic pathogen, C. albicans causes severe superficial or system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 124 publications
(109 reference statements)
0
23
0
Order By: Relevance
“…Similarly, the transcription factor b cr1 that governs the adhesion process mediated by als3 [ 34 ], the filamentation mediated by hwp1 [ 37 ], and the development of persister cells in biofilm [ 38 ] was up-regulated at 8 hpi in our study in biofilm strains. The mkc1 gene is expressed during the adhesion phase and is involved in contact-induced invasive filamentation, as well as in the maturation of biofilms [ 8 ]. This gene was up-regulated in biofilm strain at very early (4 hpi) and early (8 hpi) time points and the non-biofilm strain at 4 hpi, suggesting its role in early adhesion and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the transcription factor b cr1 that governs the adhesion process mediated by als3 [ 34 ], the filamentation mediated by hwp1 [ 37 ], and the development of persister cells in biofilm [ 38 ] was up-regulated at 8 hpi in our study in biofilm strains. The mkc1 gene is expressed during the adhesion phase and is involved in contact-induced invasive filamentation, as well as in the maturation of biofilms [ 8 ]. This gene was up-regulated in biofilm strain at very early (4 hpi) and early (8 hpi) time points and the non-biofilm strain at 4 hpi, suggesting its role in early adhesion and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that approximately 80% of C. albicans infections in humans are directly or indirectly involved with biofilm formation on the host body or abiotic surfaces, including indwelling medical devices, such as vascular catheters, prosthetic heart valves, joint replacements, or dental implants. This biofilm mostly results in high morbidity and mortality [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Als family, a class of cell wall glycoproteins, regulates cell adhesion and biofilm formation in C. albicans (Xu et al, 2022). Als1 and Als3 proteins play a vital role in adhesion to host endothelial and epithelial cells.…”
Section: Anti-adhesion Mechanisms Of Natural Productsmentioning
confidence: 99%
“…Farnesol and tyrosol are the major QS signaling molecules found in C. albicans (Davis-Hanna et al, 2008). Farnesol is an autoregulatory molecule that inhibits the yeast phase's transformation to the hypha phase (Xu et al, 2022). Farnesol is also widely distributed in propolis and fruits (Costa et al, 2021).…”
Section: Mechanisms Of Inhibiting Fungal Biofilm Formationmentioning
confidence: 99%
“…Nevertheless, despite some interspecies diversity, generally, the ability to create a biofilm gives pathogenic Candida fungi an advantage in maintaining infection and enhancing virulence potential compared with planktonic cells ( Cavalheiro and Teixeira, 2018 ). The adherence of microbial cells to biotic or abiotic surfaces, their coexistence in the community in high density, and embedding in a composite biofilm-supporting matrix not only might make the biofilm-forming cells different from free-floating ones but also contribute to acquiring novel virulence properties by the complex biofilm structure ( Xu et al., 2022 ). These are mainly related to the increased difficulty in the removal of biofilm-forming pathogens from the inhabited surfaces and to the disturbances in the effective action of antimicrobial drugs ( Ponde et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%